HADITH OF THE PROPHET CONCERNING THE INTENTIONS FROM THE PRESPECTIVE OF NOAM CHOMSKY’S TRANSFORMATIVE THEORY - Fabrori, Fahri Muhaimin (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2023)
Hadith narrated by several narrators sometimes has the same editing. From these similarities, sometimes Muslims think that there are no differences in the editorial, as well as in socio-historical aspects. Due to the existence of this problem, this research needs to be carried out to eliminate the assumption that there is no difference. This research analyzes the Prophet’s Hadith about intentions using Nosm Chomsky’s transformative generative theory, and the method used is qualitative. In this article, the author describes two hadiths about intentions which were all narrated by Imam Bukhori with almost the same editorial. However, if you look more closely, several hadith sentences are not the same, whether in the form of addition/ziyadah, al-ittisa’/expansion, or al-Ihlal/replacement. The results of this research show that the Hadith about intention number one shows that this Hadith is a form of information that is convincing and general. In the Hadith, two tawkid customs have real meanings and several redactions that do not refer to specific redactions. Meanwhile, Hadith number 52 does not contain the custom of taukid, which refers to information or just reporting. Then there is the additional sentence ila Allahi wa rasulih which shows specificity and a more complete editorial.[Hadits yang diriwayatkan oleh beberapa perawi terkadang mempunyai penyuntingan yang sama. Dari persamaan tersebut, terkadang umat Islam menganggap tidak ada perbedaan dalam redaksional, maupun dalam aspek sosio-historis. Oleh karena adanya permasalahan tersebut, maka perlu dilakukan penelitian ini untuk menghilangkan anggapan bahwa tidak ada perbedaan. Penelitian ini menganalisis Hadits Nabi tentang niat menggunakan teori transformatif generatif Nosm Chomsky, dan metode yang digunakan adalah kualitatif. Dalam artikel ini penulis memaparkan dua hadis tentang niat yang semuanya diriwayatkan oleh al-Bukhori dengan redaksi yang hampir sama. Namun jika dicermati, ada beberapa kalimat hadis yang tidak sama, baik yang berbentuk penambahan/ziyadah, al-ittisa’/perluasan, maupun al-Ihlal/pengganti. Hasil penelitian menunjukkan bahwa Hadits tentang niat nomor satu menunjukkan bahwa Hadits ini merupakan salah satu bentuk informasi yang meyakinkan dan bersifat umum. Dalam hadis tersebut terdapat dua adat tawid yang mempunyai makna nyata dan beberapa redaksi yang tidak mengacu pada redaksi tertentu. Sedangkan hadis nomor 52 tidak memuat adat taukid yang mengacu pada informasi atau sekedar pemberitaan. Lalu ada tambahan kalimat ila Allahi wa rasulih yang menunjukkan kekhususan dan redaksional yang lebih lengka].